Assessing the readability, quality and accuracy of online health information for patients with low anterior resection syndrome following surgery for rectal cancer. (4th February 2019) - Garfinkle, R.; Wong‐Chong, N.; Petrucci, A.; Sylla, P.; Wexner, S. D.; Bhatnagar, S.; Morin, N.; Boutros, M.
Abstract: Aim: Management of low anterior resection syndrome (LARS) requires a high degree of patient engagement. This process may be facilitated by online health‐related information and education. The aim of this study was to systematically review current online health information on LARS. Method: An online search of Google, Yahoo and Bing was performed using the search terms 'low anterior/anterior resection syndrome' and 'bowel function/movements after rectal cancer surgery'. Websites were assessed for readability (eight standardized tests), suitability (using the Suitability Assessment of Materials instrument), quality (the DISCERN instrument), accuracy and content (using a LARS‐specific content checklist). Websites were categorized as academic, governmental, nonprofit or private. Results: Of 117 unique websites, 25 met the inclusion criteria. The median readability level was 10.4 (9.2–11.7) and 11 (44.0%) websites were highly suitable. Using the DISCERN instrument, seven (28.0%) websites had clear aims, two (8.0%) divulged the sources used and four (16.0%) had high overall quality. Only eight (32.0%) websites defined LARS and ten (40.0%) listed all five major symptoms associated with the LARS score. There was variation in the number of websites that discussed dietary modifications (80.0%), self‐help strategies (72.0%), medication (68.0%), pelvic floor rehabilitation (60.0%) and neuromodulation (8.0%). The median accuracy of websites was 93.8% (88.2–96.7%). Governmental websites scored highest for overall suitability ( P = 0.0079) and quality ( P < 0.001). Conclusions: Current online information on LARS is suboptimal. Websites are highly variable, important content is often lacking and material is too complex for patients.